2018
DOI: 10.3390/molecules23112931
|View full text |Cite
|
Sign up to set email alerts
|

A Brief History of Charcot-Leyden Crystal Protein/Galectin-10 Research

Abstract: Eosinophils are present in tissues, such as the respiratory tract, spleen, lymph nodes and blood vessels. The significant presence of eosinophils in these tissues are associated with various diseases, including asthma, allergies, acute myeloid leukemia, etc. Charcot-Leyden crystal protein/galectin-10 is overexpressed in eosinophils and has also been identified in basophils and macrophages. In human body, this protein could spontaneously form Charcot-Leyden crystal in lymphocytes or in the lysates of lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 129 publications
(184 reference statements)
0
50
0
Order By: Relevance
“…64 Subsequent studies demonstrated that CLC/Gal-10 can weakly (nonspecifically) bind to carbohydrate under several conditions, as in its monomeric state. 65,66 In addition, recent findings indicate that Gal-10 dimerizes with a novel global shape that is different from that of other prototype galectins (eg, Gal-1, Gal-2, and Gal-7) and may essentially inhibit disaccharide binding. 65,67 The lack of binding to ß-galactosides FIG 6.…”
Section: Discussionmentioning
confidence: 99%
“…64 Subsequent studies demonstrated that CLC/Gal-10 can weakly (nonspecifically) bind to carbohydrate under several conditions, as in its monomeric state. 65,66 In addition, recent findings indicate that Gal-10 dimerizes with a novel global shape that is different from that of other prototype galectins (eg, Gal-1, Gal-2, and Gal-7) and may essentially inhibit disaccharide binding. 65,67 The lack of binding to ß-galactosides FIG 6.…”
Section: Discussionmentioning
confidence: 99%
“…This provides no independent biological way of thinking, because machines presuppose organisms". 23 Again on mechanisms, and responding to Haldane, he remarked that "it is always possible to defend microscopic mechanism in principle, if any one wishes to do so, by making your mechanism complicated enough, and by 'postulating' enough sub-mechanisms to meet all contingencies. It cannot then be refuted, but neither can it be verified.…”
Section: After the Galilean Revolution In Sciencementioning
confidence: 99%
“…So when they see something occurring in Nature at variance with their preconceived ideal of the thing in question, they believe that Nature has then failed or blundered and has left that thing imperfect" [97]. In other words, testing a model against a natural phenomenon is different than testing the said natural phenomenon against the said model, an issue which is as relevant today as it was more than 300 years ago, and harks back to the historical 23 Woodger, J. H. 1929. Biological Principles.…”
Section: Contours Of a Revived Philosophical Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Charcot-Leyden crystal (CLC) protein, also known as galectin-10, is the 10th member of the galectin superfamily of S-type lectins. CLC protein is abundant in the cytoplasm of eosinophils [7, 8] and can be crystallized during cytolytic extracellular trap cell death [9-11], before being released by activated eosinophils. CLC protein has been described for over 150 years in tissue, body fluids, and secretions of patients with a variety of eosinophilic lesions, including asthma [12], AR [13, 14], chronic rhinosinusitis (CRS) [15, 16], and other eosinophil-associated diseases [17], and regarded as a hallmark of eosinophilic inflammation.…”
Section: Introductionmentioning
confidence: 99%